SEKOLATANI: Penguatan Kapasitas Petani Perempuan untuk Produksi Hasil Pertanian Berdaya Saing Ekspor - Dody Molasy, Honest; Eko Zuhri Ernada, Sus; Dwi Eriyanti, Linda; Septian Agung Pratama, Afrizal; Athirah, Nisrina; Nursaveni, Nabillah; Saputra, Deni Eka; Ramadhani Azizah, Nafisha (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The SEKOLATANI program is a community service initiative designed to enhance the capacity and independence of women farmers in Kombongan Hamlet, Jember, in implementing export-quality organic farming practices. This intervention was motivated by the farmers' limited knowledge of sustainable agriculture and their significant reliance on chemical-based inputs. The methodology employed an educational-participatory approach, utilizing counseling, training, and hands-on practice. A learning by doing method was specifically applied to the production of organic pesticides from local natural ingredients (e.g., neem leaves, lemongrass, and galangal). The results indicated a significant increase in participants' understanding, skills, and awareness regarding sustainable land management and eco- friendly pesticide production. Furthermore, the program successfully fostered motivation among women farmers to actively contribute to household welfare and the local economy. The SEKOLATANI program demonstrates that community-based education and mentoring serve as an effective model for transforming agriculture toward more sustainable, adaptive, and gender-inclusive practices.